On the Equivalence between Two Fixed Point Theorems for Concave-Type Operators - Mohamed Jleli; Bessem Samet (Journal of Function Spaces)
In this note, we prove the equivalence between a fixed point theorem for φ–h,e–concave operators and a previous one for generalized concave operators.